The Effect of Counseling with Leaflet Media and Simulations on Knowledge and Attitudes in Breastfeeding Mothers in the Working Area of the Tanggetada Health Center, Kolaka Regency - Sukmawati, Sukmawati; Tasnim, Tasnim; Rachman, Wa Ode Nova Noviyanti (Magister Kesehatan Universitas Mandala Waluya, 2025)
Introduction: Data on breastfeeding coverage in Indonesia in 2022 shows that the figure is only 67.96%, lower than the 2021 figure of 69.7%. This shows that more comprehensive assistance is needed to increase breastfeeding rates. This study aims to analyze the effect of counseling with leaflet media and simulations on knowledge and attitudes of breastfeeding mothers in the working area of the Tanggetada Health Center, Kolaka Regency. Method: This type of research is quasi experiment. The population of this study is 60 people with a sample of 30 people. Sample withdrawal uses cluster random sampling. Data collection uses questionnaires in the form of data on respondent identity, knowledge and attitudes. Data analysis using Mann Whitney test. Result: The results of the study obtained the knowledge variable (p-value = 0,012 < α (0,05) and attitude variables (p-value = 0,011 < α (0,05). Conclusion: There are differences between leaflet media groups and simulations on knowledge and attitudes of breastfeeding mothers in the working area of the Tanggetada Health Center, Kolaka Regency.